Shear and consolidation behavior of slurry-deposited, desiccated tailings and compacted filtered tailings - Primus, Justin Michael, author; Bareither, Christopher A., advisor; Scalia, Joseph, IV, committee member; Stright, Lisa, committee member (Colorado State University. Libraries, 2024)
The objective of this study was to (i) evaluate and compare the undrained shear behavior and (ii) the consolidation behavior of slurry-deposited and desiccated tailings versus compacted filtered tailings. In general, the evaluation supports the hypothesis that desiccation and resaturation of a hard rock mine tailings yield higher peak undrained shear strengths relative to compacted filtered tailings when considering similar initial conditions (e.g., stress and density). The increase in undrained shear strength was attributed to the tailings fabric, which generated a stiffer response to loading and transitional behavior from contractive to dilative tendencies when sheared undrained. Consolidated undrained (CU) triaxial compression tests were conducted on 64-mm-diameter specimens that followed two different procedures. Slurry-deposited tailings were desiccated to a target void ratio and water content, resaturated, and tested in isotropic, consolidated, undrained axial compression. Filtered tailings specimens were prepared to similar initial void ratios as those measured on desiccated tailings specimens and tested in triaxial compression in the same manner. One-dimensional consolidation tests were also conducted on desiccated and filtered tailings specimens in a similar sequence. The desiccated and filtered tailings exhibited contractive, strain-hardening behavior in the triaxial tests and yielded effective stress friction angles of 29.1° for the desiccated tailings and 27.7° for the filtered tailings. Desiccated tailings samples showed a stiffer initial peak deviatoric stress and slower decreasing rate of change in stress relative to the filtered tailings. There was no indication of a difference in stiffness or brittleness between tailings preparation methods. The higher shear strength of the desiccated tailings was attributed to (i) more pronounced inter-particle reinforcing effects and (ii) densification from stress-history of desiccation. One-dimensional consolidation tests yielded a trend of increasing preconsolidation pressure with decreasing initial void ratio for both the desiccated and filtered tailings. There were slightly higher average compression and recompression indexes computed for the desiccated tailings relative to the filtered tailings, providing an indication of the different in the fabric behaviors.
Keywords: desiccation; strength; undrained; shear; consolidation; tailings